1342. Clinical failure rates of amoxicillin for the treatment of acute otitis media in young children. (31st December 2020) - Frost, Holly M; Dominguez, Samuel; Parker, Sarah; Byars, Andrew; Michelson, Sara; Keith, Amy; Jenkins, Timothy C
Abstract: Background: Acute otitis media(AOM) is the most common indication for antibiotics in children. The primary pathogens that cause AOM have changed since the introduction of the pneumococcal conjugate vaccine(PCV). The clinical failure rate of amoxicillin for treatment of AOM post-PCV is unknown.We aimed to determine the clinical failure rate of amoxicillin for the treatment of uncomplicated AOM in children. Organisms identified on culture and amoxicillin treatment failure from nasopharyngeal specimens of children age 6-35 months with uncomplicated acute otitis media at Denver Health, Denver, CO from April 2019-March 2020. Methods: Children age 6-35 months seen at Denver Health, Denver, CO with uncomplicated AOM and prescribed amoxicillin were prospectively enrolled. An interim analysis of patients enrolled from April 2019-March 2020 was completed. Patients completed surveys that included the AOM-SOS©(UPMC, Pittsburgh, PA) at enrollment, days 5, 14, and 30 and had chart abstraction completed. Treatment failure was defined as: (1) requiring a new antibiotic within 14 days; (2) AOM-SOS© score on day 5 or 14 not improved by a relative reduction of ≥ 55% from baseline. Recurrence was defined as requiring a new antibiotic within 15-30 days. Nasopharyngeal swabs were obtained and bacterial culture was completed. Results: In total, 110 patients were enrolled. Rates of treatment failure defined by AOM-SOS© were 28.4%(37; 95%CI:25.5-33.6%) at 5 days and 15.5%(27; 95%CI:17.5-24.5%) at 14 days. However, only 4.5%(5; 95%CI:2.0-4.5%) required a new antibiotic. Recurrence occurred in 5.5% (6, 95%CI:2.5-5.5%) of patients. Of patients who had not received antibiotics before enrollment(82), culture yielded no organism in 17.0%, one organism in 42.7%, and multiple organisms in 40.0% (Table ). M.catarrhalis was the most frequently identified organism (53.7% of children). Of H.influenzae isolates 52.9% (9/17) produced beta-lactamase, resulting in no treatment failures or recurrences requiring a new antibiotic. Failure rates were similar between organisms. Conclusion: Despite the change in otopathogen prevalence post-PCV, preliminary data suggest that while early subjective treatment failure was common, the 14 day treatment failure and 30 day recurrence rates was low when measured by need for a new antibiotic. Failure was low even among patients with organisms that would not be expected to be treated successfully with amoxicillin, such as those with beta-lactamase producing H.influenzae and M.catarrhalis. Disclosures: Samuel Dominguez, MD, PhD, BioFire (Consultant, Research Grant or Support)